A robust maximum power point tracking control for PV panel using adaptive PI controller based on fuzzy logic - Slamet Slamet; Estiko Rijanto; Asep Nugroho; R. A. Ghani (Universitas Ahmad Dahlan, 2020)
Most methods of maximum power point tracking (MPPT) for photovoltaic (PV) focus only on tracking performance while robustness against disturbances hasrarely been addressed. This paper proposes a new MPPT control method that provides robustness against direct current (DC) link voltage disturbance as well as good tracking performance. The method uses indirect MPPT control topology which incorporates two controllers. For the external controller, we use an adaptive proportional-integral (PI) control which is real-time tuned by fuzzy logic (FL). New membership functions and rule base are proposed using only one fuzzy input variable and 10 fuzzy rules. The internal controller is a PI controller. The PV panelis connected to a boost DC-DC converter. The proposed MPPT control iscompared with the fuzzy logic controller (FLC). Performance is evaluated under DC link voltage disturbance, steady-state condition, and rapid solar radiation changes. Simulation results indicate that the proposed method provides 41.2 % better robustness against DC link voltage disturbance as compared to the direct FLC. Experimental results under natural climate conditions with real solar radiation validate that the proposed method works well in regulating the MPP at steady-state solar irradiance as well as in tracking the MPP towards rapid solar irradiance changes. It yields the PV power tracking speed of 95.75 W/s.